1972
DOI: 10.1136/jech.26.4.249
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and smoking habits by social class.

Abstract: In a recent paper we reported that there are considerable differences in the body weights of men categorized by their smoking habits (Khosla and Lowe, 1971). In a population of 10,482 steel workers we found that the men who had never smoked were much heavier than the smokers and that the men who had given up smoking for eight or more years were almost as heavy as those who had never smoked. The difference between the weights of non-smokers and smokers increased with age to the extent that over 40 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…between the fat advice and no advice groups for fat as a percentage of energy was least for those with a BMI of 30 or more. BMI is positively associated with social class (Khosla & Lowe, 1972;Kohrs et al, 1979;Rose 81 Marmot, 1981;Fehily et al, 1984) but social class is unlikely to be a confounding factor since the effect of fat advice did not vary with social class. The most likely explanation is that since all overweight men were given weight reducing advice they would have reduced their fat intake to some extent, thereby reducing the difference between the fat advice and no advice groups.…”
Section: Discussionmentioning
confidence: 97%
“…between the fat advice and no advice groups for fat as a percentage of energy was least for those with a BMI of 30 or more. BMI is positively associated with social class (Khosla & Lowe, 1972;Kohrs et al, 1979;Rose 81 Marmot, 1981;Fehily et al, 1984) but social class is unlikely to be a confounding factor since the effect of fat advice did not vary with social class. The most likely explanation is that since all overweight men were given weight reducing advice they would have reduced their fat intake to some extent, thereby reducing the difference between the fat advice and no advice groups.…”
Section: Discussionmentioning
confidence: 97%
“…37 We computed the body mass index (BMI) using the widely accepted method ofweight (kg) divided by the square of height (m2) . 38 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 884 24 70 (3 18) 488 24-64 (328) In the analyses of the proportion of overweight 7055 24 24 When the RR is larger than 1, the OR is always 6288 24-25 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) 5345 24-40 (3-22) larger than the RR, and for large absolute risks the 242 23-32 (3-25) 276 23-86 .…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have reported an inverse relation between sociodemographic status and obesity in women. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The associations found between sociodemographic factors and obesity in men, however, have been weaker, more variable, and 6 18-22 24-29 31-35 less consistent.…”
mentioning
confidence: 99%
“…An increase of 0 74 kg/M2 for a woman 168 cm tall corresponds to a weight increase of more than 2 kg. In the various socioeconomic groups, women classified as senior salaried employees and self employed professionals showed the greatest increase-a [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (1-74) -0-04 (0 39) All socioeconomic group 20-73 (0 11) 0-18 (0-06)t * p<005; t p<0 0005; t p<0-005 highly significant one-in mean BMI in 1988-89 compared with 1980-81 (0 79 kg/r2, p<0 0005), and they are followed by a group of manual workers (0-21 kg/M2, p<0 005). Increases in other groups were smaller and not significant.…”
Section: Eight Year Trends In Mean Bmimentioning
confidence: 98%